2017
DOI: 10.1038/nrneurol.2017.81
|View full text |Cite
|
Sign up to set email alerts
|

Autologous haematopoietic stem cell transplantation for treatment of multiple sclerosis

Abstract: Autologous haematopoietic stem cell transplantation (AHSCT) is a multistep procedure that enables destruction of the immune system and its reconstitution from haematopoietic stem cells. Originally developed for the treatment of haematological malignancies, the procedure has been adapted for the treatment of severe immune-mediated disorders. Results from ~20 years of research make a compelling case for selective use of AHSCT in patients with highly active multiple sclerosis (MS), and for controlled trials. Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
217
0
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(238 citation statements)
references
References 109 publications
6
217
0
15
Order By: Relevance
“…Autologous hematopoietic stem cell transplantation (AHSCT) is a well-proven treatment used predominantly for blood malignancies, but also for solid tumors and inflammatory diseases such as multiple sclerosis (MS) and systemic sclerosis [1][2][3]. Although the removal of malignant cells is assumed to be a key aspect in the treatment of lymphomas and myelomas, less is known about the mechanisms behind the improvements seen in patients with inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous hematopoietic stem cell transplantation (AHSCT) is a well-proven treatment used predominantly for blood malignancies, but also for solid tumors and inflammatory diseases such as multiple sclerosis (MS) and systemic sclerosis [1][2][3]. Although the removal of malignant cells is assumed to be a key aspect in the treatment of lymphomas and myelomas, less is known about the mechanisms behind the improvements seen in patients with inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale behind AHSCT is that high dose chemotherapy may eradicate autoreactive lymphocyte clones while the infusion of haematopoietic stem cells may reconstitute a tolerant immune system, possibly by renewed thymic output 16. Immune reconstitution (IR) of patients with MS post-AHSCT suggests that transplantation removes putative proinflammatory lymphocytes such as mucosal-associated invariant T (MAIT) cells17 while regenerating immunoregulatory populations such as CD39 + T regulatory cells,18 CD56 high natural killer (NK) cells19 and suppressor CD8 + CD57 + T cells,17 some of which are recognised to be dysfunctional in MS 18.…”
Section: Introductionmentioning
confidence: 99%
“…56 In this scenario, studies have shown that donor-derived Bregs are important for suppression of murine sclerodermatous chronic graft-versus-host disease. 72 In the present study, we found a correlation between favorable clinical outcomes and Breg levels after AHSCT in SSc patients.…”
Section: Cd19mentioning
confidence: 99%